IMPLEMENTATION OF THE LEARNING CYCLE 7E MODEL IN LEARNING THE CONCEPT OF REACTION RATES - Latifah Hanum; Hulfa Harnisah; Ade Ismayani (FKIP USK, 2020)
The purpose of this study is to describe the activities of students, the completeness of student learning outcomes, and student responses to the 7E learning cycle learning model on the reaction rate material. This is a descriptive study with a qualitative approach. The sample in this study was 28 students of class XI MIA-3 at SMAN 5 Banda Aceh. The instruments used in this study were student activity observation sheets, test question sheets, and student response questionnaire sheets. The overall activity of students increase from time to time. The results of observing student activities in the seven stages of the 7E learning cycle model obtained an average of 87.63% of student activity at the elicit stage, 91.75% engage stage, 94.38% explore stage, 83.38% explain stage. , elaborate stage 70.88%, evaluate stage 79.13%, and extend stage 87.13%. The highest activity is at the explore stage. The average percentage of classical student learning outcomes is 75% with a good category. Positive responses from students were obtained by 80.77%. Based on the results of the research that has been done, it can be concluded that the application of the 7E learning cycle model can complete the classical learning of students. Overall student activity has increased and the highest activity is in the explore stage and students give good responses to the application of the 7E learning cycle learning model.